1992
DOI: 10.1088/0957-0233/3/9/018
|View full text |Cite
|
Sign up to set email alerts
|

Digital deconvolution analysis of ultrasonic signals influenced by the presence of longitudinally aligned steel cables in pre-stressed concrete

Abstract: Several experiments are described in which ultrasonic signals were transmitted and received through concrete containing steel rods and cables. Details of how the signals were processed to extract information relating to the condition of the steel itself are presented. In particular, the method deconvolution is employed in a manner which allows the impulse response and frequency response of the embedded steel alone to be uniquely isolated from the effects of the surrounding concrete, whilst still allowing the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 3 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…The results indicated that the received signal increases as the amount of debonding increases. Gaydecki et al (1992) embedded a #2 (0.25 in or 7 mm diameter) steel wire into a concrete mix with 4% calcium chloride solution added to induce corrosion. The reinforced concrete specimen was cylindrical, with an outer diameter of 150 mm (5.91 in) and a length of 1 m (39.37 in).…”
Section: De-bonding Studiesmentioning
confidence: 99%
“…The results indicated that the received signal increases as the amount of debonding increases. Gaydecki et al (1992) embedded a #2 (0.25 in or 7 mm diameter) steel wire into a concrete mix with 4% calcium chloride solution added to induce corrosion. The reinforced concrete specimen was cylindrical, with an outer diameter of 150 mm (5.91 in) and a length of 1 m (39.37 in).…”
Section: De-bonding Studiesmentioning
confidence: 99%
“…However, both low and high frequencies caused increase in signal strength. Other effects such as loading conditions [6], reinforcing ribs [8,9,12], corrosion products [9,13], and anchorages [8] on the guided waves have been reported. Reis et al [11] used fundamental flexural mode at frequencies below 250 kHz for estimation of corrosion damage in steel reinforced mortar.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive literature describes the uses of SAFT to investigate concrete structures [23][24][25][26] and metals, including aluminium [19][20][21] and steel pipes [14,27]. Although this type of ultrasonic imaging has been widely used for Non-destructive Evaluation (NDE) with a moving array of sensors, its application to structural health monitoring is not straightforward and requires the algorithm to be adapted to an array of multiple static transducers.…”
Section: Principle and Evolution Of Defect Imaging With Total Focusinmentioning
confidence: 99%